The effect of job crafting on work performance: Mediating role of work engagement and social capital - Mahardian Dewo Negoro; Johan Suseno; Rifaizal Samual; Adhary Mahaputera Darmawan; Amin Akbar (Jurnal Fokus Manajemen Bisnis, 2025)
Police as law enforcement officers often have limited means to achieve their work performance. Therefore, job crafting skills are important to obtain optimal work performance. This research analyzes the direct and indirect influence of job crafting on work performance through work engagement and social capital. The research method used was explanatory research with research samples consisting of members of the Indonesian National Police from various units spread throughout Indonesia. The sample number in this research was 601 police officers who had worked for at least one year, taken using convenience sampling. Partial least squares structural equation modeling is the method of analysis employed. According to the study's findings, job crafting improves work engagement, job crafting improves social capital, job crafting improves job work performance, work engagement improves work work performance, and social capital improves work work performance. Through work engagement and social capital, job crafting has a favorable and significant impact on work work performance for Indonesian National Police personnel. This study suggests that job making skills can be used to improve the work work performance of Indonesian National Police personnel. This research has limitations is the sample obtained was not taken proportionally per the regional police legal area in Indonesia.